Efeitos do treinamento muscular inspiratório em indivíduos adultos obesos: uma revisão sistemática - Rios, Manoela Pinto (2024)
The excess weight, classified as obesity, is a significant public health problem worldwide and causes multisystemic alterations. Specifically, obesity compromises the respiratory system, leading to early onset of dyspnea and exercise intolerance, which impacts the quality of life of these individuals. Inspiratory muscle training (IMT) is a form of ventilatory exercise used in various patients, aiming to increase the strength and endurance of the inspiratory muscles. This can lead to improved functional capacity and quality of life. Although the results of IMT in obese individuals are promising, there is currently no consensus on its effectiveness in this adult population. The aim of this study was to systematically review the effects of IMT on inspiratory muscle strength, diaphragmatic mobility, lung function, and functional capacity in adult obese individuals. The search strategy was conducted on electronic databases including MEDLINE, Cochrane CENTRAL, Embase, Scopus, and PEDro. The search strategy followed the PICOS system, selecting the following sections: P (population): obese individuals, I (interventions): Inspiratory Muscle Training, S (study design): randomized controlled trials, with no restrictions on publication date or language. Studies that conducted IMT in obese adults were included if they assessed maximum inspiratory pressure, diaphragmatic mobility, forced expiratory volume in the first second, forced vital capacity, Tiffeneau index and/or distance walked in the six-minute walk test. Selection of studies based on title, abstract, and full text, as well as assessment of bias risk and methodological quality, was performed independently by two reviewers. The initial search yielded 2,214 articles, from which 5 were included in the review. Data from these studies were extracted and entered into a standardized form previously developed by the researchers. Meta-analysis was conducted using a random-effects model, and results were presented as mean differences with 95% confidence intervals. The risk of bias was assessed using the RoB 2.0 tool, and the quality of evidence was evaluated using the GRADE system. IMT was found to increase inspiratory muscle strength, as indicated by an increase in PImax of 0.998 (95% CI 0.657 to 1.340; p=0.001; I2: 2%). Additionally, IMT led to improved functional capacity, measured by an increase in the distance walked during the six-minute walk test of 0.875 (95% CI 0.481 to 1.268; p=0.001; I2: 0%). However, IMT did not alter lung function parameters such as FEV1 [SMD= -0.03; 95% CI -0.351 to 0.079; p=0.821; I2: 0%], FVC [SMD= -0.276; 95% CI -0.596 to 0.040; p=0.086; I2: 0%], and the Tiffeneau index [SMD= -0.360; 95% CI -0.974 to 0.255; p=0.251; I2: 0%]. Our study results demonstrate that Inspiratory Muscle Training is an intervention capable of improving inspiratory muscle strength and functional capacity in adult obese individuals.